The Implementation of Remedial Teaching in Assisting Second Language Learner - Maulana Yusuf Aditya (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2018)
Many students get a low achievement in their learning. One of the suggested ways in overcoming the students’ problems is remedial teaching. Contrary to the procedure, remedial teaching was mostly done perfunctorily. This study was generally aimed to find out how teachers apply the remedial teaching in class. Specifically, this study was aimed to find out how teachers identifying students who need to be given remedial teaching, how teachers find the students difficulties in their learning process and how teachers devise strategies to overcome the students’ problems. In this study the researcher gathered data on the implementation of remedial teaching in senior high school. The focus of the study was the implementation of remedial teaching on English lesson on the students of SMAN 3 Bangkalan only. A qualitative research design was proposed to obtain answers to research questions of this study. The study that the researcher chose was case study. The subject of this research was English teachers of the Tenth Grade Students of SMAN 3 Bangkalan. To collect data the researcher did observation, interview and documents gathering. The research finding was the implementation of remedial teaching in SMAN 3 Bangkalan was quite good, but it was not too much well done. English teachers of SMAN 3 Bangkalan did the remedial teaching by analyzing the students’ score, analyzing the students’ disabilities and curing the students’ disabilities. But the enrichment program had not conducted yet. They did the all steps of the remedial teaching but there were several that they ignored. It was done unmaximally. And there was lack of teachers’ role. Nevertheless, the implementation of remedial teaching in SMAN 3 Bangkalan was not done too much perfunctorily. It could be said that it was had only a few methodological flaws